Mitochondrial genome of a typical cavefish of Sinocyclocheilus anatirostris - Xinrui Zhao; Changting Lan; Jing Yu; Jiajun Zhou; Xueli Lu; Ning Xiao; Huaiqing Deng; Jiang Zhou (Mitochondrial DNA. Part B. Resources, 2023)
Sinocyclocheilus anatirostris Lin and Luo, 1986 is a member of the endemic Chinese genus Sinocyclocheilus Fang, 1936, living in dark caves with absence of eyes and scales. Muscle tissue was collected from cavefish samples from Guangxi, China, and complete mitogenome was sequenced. This is the first report of the mitogenome of S. anatirostris. This mitogenome consists of 13 protein-coding genes (PCGs), two rRNA genes (12S rRNA and 16S rRNA), 22 tRNA genes, a control region (CR), and comprises 31.2% A, 24.4% T, 16.7% G, and 27.7% C bases. Phylogenetically, S. anatirostris is closely related to the Sinocyclocheilus furcodorsalis, and originated in the late Miocene, ∼6.07 Ma.